Role of Spacenet in Sharing Digital Resources among ISRO Libraries - Prasada Rao, A.B.S.V.I; Laxmi, Ashalatha (DESIDOC Journal of Library & Information Technology, 2010)
Spacenet is a Closed User Group (CUG)-based communication network of Department of Space/Indian Space Research Organisation (ISRO) catering to a variety of space community needs. It offers wide range of potential benefits both to libraries and end-users across the ISRO centres in India. Over a decade, Spacenet has evolved as a community network for the space community in India. The paper explains how the resources of various ISRO information centres are shared/utilised, digital libraries (DL) built, accessed, and institutional repositories (IRs) organised among the libraries using Spacenet. http://dx.doi.org/10.14429/djlit.29.262